Vision of the Reich Film Industry - Skopal, Pavel (Iluminace, 2018)
This edition of archival documents, with an introductory study by Pavel Skopal, presents internal reports from the management of the German film industry from 1942 and 1944, which, in the context of the war, address film export strategies, the significant economic contribution of the Protectorate of Bohemia and Moravia to revenues, and the ideological and pragmatic aspects of using foreign film stars.
Keywords: Reich film industry; film exports; Ufa; Protectorate of Bohemia and Moravia; film stars